2019
DOI: 10.1002/adem.201900540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filter Functional Coating on Detrimental Nonmetallic Inclusions in 42CrMo4 Steel and Its Resulting Mechanical Properties

Abstract: Carbon‐bonded ceramic foam filters with different functional coatings are immersed in a 42CrMo4 steel melt within a steel casting simulator. The solidified steel is analyzed with respect to the size distribution and the chemical composition of the remaining nonmetallic inclusions (NMI). Cyclic loading and quasi‐static tests are performed to determine the fatigue limit, the strength, deformability, and toughness of the steel after filter immersion. The immersion of filter with calcium hexaluminate (CA6) coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Due to the surface protection by nitriding, all of the investigated fatigue cracks were originated from the interior with a clearly recognizable fisheye (Figure 2A,D). Corresponding stress versus cycles to failure ( S‐N f ) curves are not in the focus of present work and can be found elsewhere 32 . Most of the fatigue cracks were initiated by a plate‐shaped Al 2 O 3 particle, surrounded with FGA in case of N f ≥ 10 6 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the surface protection by nitriding, all of the investigated fatigue cracks were originated from the interior with a clearly recognizable fisheye (Figure 2A,D). Corresponding stress versus cycles to failure ( S‐N f ) curves are not in the focus of present work and can be found elsewhere 32 . Most of the fatigue cracks were initiated by a plate‐shaped Al 2 O 3 particle, surrounded with FGA in case of N f ≥ 10 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Following the above‐mentioned assumption, the SA should be somehow related with the plastic zone size and martensitic structure. The size of the cyclic plastic zone around a propagating fatigue crack can be estimated by a radius r c , which starts from the crack tip and ends at the local stress level equal to the yield strength σ YS 21 ,p. 306 rnormalc0.25emSA1πΔKeff0.25emSA2σYS23.610.25emμm, where σ YS = 950 MPa is the yield strength of the analysed 42CrMo4 steel 32 . This value matches almost perfectly with the average grain size of 3.63 μm, which corresponds to the average size of a martensite block (Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, an average value of ΔK th = 7.0 ± 2.2 MPa√m for all failed specimens was determined using the √area parameter of Murakami 18 and the polygon method to determine the defects' area. Stanzl-Tschegg et al 1,12 and Seleznev et al 50 also reported on lower surface roughness at the inner FIE, the so-called 'smooth area' for RT fatigue experiments. In the VHCF regime, the surface roughness inside the FiE is connected to the crack growth rate.…”
Section: Influence Of Defectsmentioning
confidence: 96%
“…Other authors evaluated values of SIF for FGA formation from 4 up to 5 MPa√m. 12,[48][49][50][51] Li et al 52 reported a SIF threshold value of 6.5 MPa√m for the formation of an FGA. In the present study, an average value of ΔK th = 7.0 ± 2.2 MPa√m for all failed specimens was determined using the √area parameter of Murakami 18 and the polygon method to determine the defects' area.…”
Section: Influence Of Defectsmentioning
confidence: 99%